Sustainable cities in developing countries : theory and practice at the millennium - Pugh, Cedric D. J. (London ; Sterling, VA : Earthscan, 2005)
Sustainable Cities in Developing Countries aims to establish ground rules for the burgeoning sphere of urban studies. Topics covered include reflections on sustainable urban development, localisation of Agenda 21 and low-income living areas.
Includes bibliographical references and index.
Keywords: City planning -- Developing countries; Sustainable development; Urban ecology (Sociology) -- Developing countries